Composite material proton exchange membrane and preparation method thereof

By physically mixing the sulfonic acid functionalized polyvinyl fluoride resin and the sulfonic acid functionalized polyvinyl fluoride styrene resin to form a proton exchange membrane, solving the problems of limited application and low mechanical strength of existing materials in high temperature and low humidity environments, and achieving efficient and low-cost proton exchange membrane production.

CN116253963BActive Publication Date: 2025-04-08SHANGHAI 3F NEW MATERIAL TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211690840.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-27
Publication Date
2025-04-08
Estimated Expiration
2042-12-27

AI Technical Summary

Technical Problem

The existing proton exchange membrane materials are limited in high temperature and low humidity environments, have low mechanical strength and high production costs, and the mechanical properties are deteriorated by comonomers and are difficult to industrialize.

Method used

Physical mixing of sulfonic acid functionalized polyvinyl fluoride resin and sulfonic acid functionalized polyvinyl fluoride styrene resin is used to form a proton exchange membrane through casting and evaporation, avoiding covalent bonding, simplifying the process and reducing costs.

Benefits of technology

It achieves the maintenance of excellent proton conductivity at high temperatures, significantly improves mechanical properties and chemical stability, reduces production costs, and is simple and easy to perform.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116253963B_ABST
    Figure CN116253963B_ABST
Patent Text Reader

Abstract

The present application provides a composite material and a preparation method thereof. The composite material comprises a sulfonic acid functionalized polyvinyl fluoride resin and a sulfonic acid functionalized polyfluorinated styrene resin physically mixed with each other, based on the total weight of the composite material. The composite material can be used to synthesize a proton exchange membrane by a solution casting method. The composite material of the present invention and the proton exchange membrane manufactured by the composite material can be synthesized by a low-cost and simple process, and have excellent proton conductivity, a high operating temperature, excellent mechanical strength and suitable water absorption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and more specifically to a composite material suitable for a proton exchange membrane of a battery and a preparation method thereof. Background Art

[0002] Fuel cell vehicles are one of the main technical paths for the development of new energy vehicles in my country. As the heart of fuel cell vehicles, the fuel cell stack has the membrane electrode as its most critical component, and the proton exchange membrane is the core material in the membrane electrode.

[0003] At present, the commercialized proton exchange membranes in the world are mainly made of various fluorinated resins or perfluoro resins. These proton exchange membranes can achieve basically satisfactory proton conductivity and chemical stability, but these materials also have problems that cannot be overcome. For example, the monomer synthesis of the commonly used sulfonic acid functionalized perfluoropolyethylene resin material is complex and expensive. In addition, the glass transition temperature Tg of this resin material is about 100°C, which significantly limits its application in the high temperature and low humidity environment that fuel cells often experience. In addition, the mechanical strength of this resin material is relatively low, only 20-40MPa, and it needs to be reinforced with an additional mechanical reinforcement membrane.

[0004] In order to solve the above problems, many researchers have invested a lot of cost and energy to conduct research, but so far people's thinking is mainly to add a certain amount of various comonomers in the process of synthesizing sulfonic acid functionalized perfluoropolyethylene resin, and the examples of these comonomers include fluorinated styrene, substituted fluorinated styrene, etc. However, the research results are quite disappointing. After these comonomers are introduced into the main chain structure of sulfonic acid functionalized perfluoropolyethylene resin in various proportions, the mechanical properties of the obtained governance exchange membrane will be significantly deteriorated (flexibility and elongation at break will be deteriorated), causing it to be easily brittle and broken. Another significant problem is that the copolymerization compatibility of sulfonic acid functionalized perfluoropolyethylene resin and various comonomers is poor, and the copolymerization reaction cannot obtain a copolymer product with satisfactory performance, or the yield of the copolymer product is very low. The defects of the above-mentioned various prior arts make it impossible to truly industrialize the research based on the copolymerization technology of sulfonic acid functionalized perfluoropolyethylene resin.

[0005] Therefore, the art is eager to develop a new technology that can synthesize a composite material of sulfonic acid functionalized perfluoropolyethylene resin and other performance-improving components in a convenient and low-cost manner, and the composite material can exhibit satisfactory proton exchange performance and significantly improved mechanical properties, water absorption, etc. Summary of the invention

[0006] In view of the above problems, the inventors of the present application conducted in-depth research and successfully developed a method and material that is completely different from the copolymerization process in the prior art, thereby effectively solving the long-standing problem in the prior art that urgently needs to be solved.

[0007] The first aspect of the present application provides a composite material, which comprises 0.1-99.9 wt % of a sulfonic acid functionalized polyvinyl fluoride resin and 0.1-99.9 wt % of a sulfonic acid functionalized polyfluorinated styrene resin, based on the total weight of the composite material, wherein the sulfonic acid functionalized polyvinyl fluoride resin and the sulfonic acid functionalized polyfluorinated styrene resin are physically mixed with each other.

[0008] The second aspect of the present application provides a method for manufacturing the composite material of the present invention, the method comprising: step one: dissolving the sulfonic acid functionalized polyvinyl fluoride resin and the sulfonic acid functionalized polystyrene fluoride resin in a solvent to form a solution or dispersion; step two: coating the solution or dispersion on the surface of a substrate to form a coating film; and step three: drying the coating film to obtain the composite material.

[0009] The third aspect of the present application provides a proton exchange membrane, wherein the proton exchange membrane comprises a membrane formed by the composite material of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] In the following paragraphs, various embodiments of the present application are discussed in conjunction with the accompanying drawings. However, it should be noted that the embodiments shown in the accompanying drawings and described in detail below are only some preferred embodiments of the present application, and the scope of protection of the present application is defined by the claims, but is not limited to these preferred embodiments. In addition, for the purpose of clear display, the reactors and various components shown in the drawings of the specification are not drawn according to the true scale.

[0011] Figure 1 A flow chart showing a method according to one embodiment of the present application;

[0012] Figure 2 A schematic diagram of a proton conducting membrane according to one embodiment of the present application is shown. DETAILED DESCRIPTION

[0013] "Range" disclosed herein is in the form of lower limit and upper limit. It can be one or more lower limits, and one or more upper limits respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundaries of a particular range. All ranges that can be defined in this way are inclusive and combinable, i.e. any lower limit can be combined with any upper limit to form a range. For example, a range of 60-120 and 80-110 is listed for a particular parameter, and it is understood that a range of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5.

[0014] In this application, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations.

[0015] In this application, unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined with each other to form a new technical solution.

[0016] In this application, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.

[0017] In this application, if there is no special explanation, the "including" mentioned herein means open or closed. For example, the "including" may mean that other components not listed may also be included, or only the listed components may be included.

[0018] The present application has developed a composite material, which, based on the total weight of the composite material, comprises 0.1-99.9 weight % of a sulfonic acid functionalized polyvinyl fluoride resin and 0.1-99.9 weight % of a sulfonic acid functionalized polystyrene fluoride resin, wherein the sulfonic acid functionalized polyvinyl fluoride resin and the sulfonic acid functionalized polystyrene fluoride resin are physically mixed with each other. One of the inventive points of the present application is that the sulfonic acid functionalized polyvinyl fluoride resin and the sulfonic acid functionalized polystyrene fluoride resin are synthesized separately, then mixed by dissolution, and then formed into a product proton conducting membrane by casting and evaporation, so that in the composite material, the two resins are physically mixed. According to some embodiments of the present application, there is no covalent bond between the sulfonic acid functionalized polyvinyl fluoride resin and the sulfonic acid functionalized polystyrene fluoride resin, and the two are merely a simple physical mixture.

[0019] According to one embodiment of the present application, based on the total weight of the composite material, the content of the sulfonic acid functionalized polyvinyl fluoride resin can be 0.1-99.9% by weight, for example, 1-99% by weight, or 5-95% by weight, or 10-90% by weight, or 15-85% by weight, or 20-80% by weight, or 25-75% by weight, or 30-70% by weight, or 35-65% by weight, or 40-60% by weight, or 45-55% by weight, or 48-50% by weight, or the content of the sulfonic acid functionalized polyvinyl fluoride resin can be within the numerical range obtained by combining any two of the above end values.

[0020] According to another embodiment of the present application, based on the total weight of the composite material, the content of the sulfonic acid functionalized polyfluorinated styrene resin can be 0.1-99.9 weight %, for example, 1-99 weight %, or 5-95 weight %, or 10-90 weight %, or 15-85 weight %, or 20-80 weight %, or 25-75 weight %, or 30-70 weight %, or 35-65 weight %, or 40-60 weight %, or 45-55 weight %, or 48-50 weight %, or the content of the sulfonic acid functionalized polyfluorinated styrene resin can be within the numerical range obtained by combining any two of the above end values.

[0021] According to one embodiment of the present application, the composite material is entirely composed of the sulfonic acid functionalized polyvinyl fluoride resin and the sulfonic acid functionalized polyfluorinated styrene resin without containing any other components.

[0022] According to another embodiment of the present application, in addition to the sulfonic acid functionalized polyfluoroethylene resin and the sulfonic acid functionalized polyfluorostyrene resin, the composite material may also contain other components conventionally used in proton exchange membranes as needed, examples of which may include: carbonaceous materials, such as carbon black, graphite, nanocarbon or fullerene; metal oxides or non-metallic oxides, such as transition metal oxides, silicon dioxide, etc.; metal particles, such as metal nanoparticles; one or more other polymers or resins, such as polysulfone, polyimide, polyaniline, polypyrrole; additives, such as adhesives, mechanical reinforcing agents, fillers, etc. When these other components are present, based on the total weight of the composite material, the content of each of the other components may be ≤0.1% by weight, or ≤0.5% by weight, or ≤1% by weight, or ≤2% by weight, or ≤3% by weight, or ≤4% by weight, or ≤5% by weight, or ≤6% by weight, or ≤7% by weight, or ≤8% by weight, or ≤9% by weight, or ≤10% by weight, or may be within the numerical range obtained by combining any two of the above end values.

[0023] According to one embodiment of the present application, the sulfonic acid functionalized polyvinyl fluoride resin comprises a component having a structure shown in Formula I, or is entirely composed of a substance having a structure shown in Formula I:

[0024]

[0025] According to one embodiment of the present application, in Formula I, M is an integer from 0 to 6000, for example, an integer from 1 to 5500, or an integer from 2 to 5000, or an integer from 5 to 4000, or an integer from 8 to 3000, or an integer from 10 to 2000, or an integer from 15 to 1000, or an integer from 20 to 600, or an integer from 25 to 500, or an integer from 30 to 400, or an integer from 35 to 300, or an integer from 40 to 200, or an integer from 50 to 150, or an integer from 60 to 120, or an integer from 80 to 100, or the numerical value of M may be within the range obtained by combining any two of the above end values.

[0026] According to another embodiment of the present application, in Formula I, N is an integer of 5 to 6000, for example, an integer of 8 to 5000, or an integer of 10 to 4000, or an integer of 12 to 3000, or an integer of 15 to 2000, or an integer of 20 to 1000, or an integer of 25 to 700, or an integer of 30 to 600, or an integer of 40 to 500, or an integer of 50 to 400, or an integer of 60 to 300, or an integer of 70 to 200, or an integer of 80 to 150, or an integer of 90 to 120, or an integer of 100 to 110, or the numerical value of N may be within the range obtained by combining any two of the above end values.

[0027] According to another embodiment of the present application, the ratio of M to N is 0:100 to 99:1, for example 5:95 to 95:5, or 10:90 to 90:10, or 15:85 to 85:15, or 20:80 to 80:20, or 30:70 to 70:30, or 40:60 to 60:40, or 45:55 to 50:50, or the ratio of M to N can be within the range obtained by combining any two of the above end values.

[0028] According to one embodiment of the present application, in the compound shown in Formula I, each of the [CF2-CF2] polymerization unit and the [CF(-X-SO3A)-CF2] polymerization unit can be distributed in the polymer main chain in any form, for example, these two polymerization units can be distributed in the polymer main chain in a random or block form.

[0029] According to another embodiment of the present application, X is a divalent group having a structure selected from the following: -[OCF2CF(CF3)] x -O[CF2] y -,-O[CF2] y -[OCF2CF(CF3)] x -, the left side of the divalent group shown above is connected to [CF-CF2] in the main chain by a covalent bond, and the right side is connected to -SO3A by a covalent bond. According to another embodiment of the present application, x is an integer of 0, 1, 2, 3, 4, 5 or 6, preferably x is an integer of 0 or 1. According to another embodiment of the present application, y is an integer of 1, 2, 3, 4, 5, 6, 7 or 8, preferably 2, 3 or 4. According to another embodiment of the present application, A is selected from at least one of the following: hydrogen ion, metal cation, ammonium ion, organic amine cation, phosphonium cation, preferably hydrogen ion.

[0030] According to one embodiment of the present application, the equivalent weight of the sulfonic acid functionalized polyvinyl fluoride resin is 500-8000 g / mol, for example, 600-7000 g / mol, or 700-6000 g / mol, or 800-5000 g / mol, or 900-4000 g / mol, or 1000-3000 g / mol, or 1500-2000 g / mol, or within the range obtained by combining any two of the above end values.

[0031] According to another embodiment of the present application, the weight average molecular weight of the sulfonic acid functionalized polyvinyl fluoride resin can be 10,000-1,000,000, for example, 20,000-800,000, or 30,000-600,000, or 40,000-500,000, or 50,000-400,000, or 60,000-200,000, or 80,000-150,000, or 100,000-120,000, or within the numerical range obtained by combining any two of the above end values.

[0032] According to one embodiment of the present application, the sulfonic acid functionalized polyfluorinated styrene resin comprises a component having a structure shown in Formula II, or is entirely composed of a substance having a structure shown in Formula II:

[0033]

[0034] According to one embodiment of the present application, in Formula II, m is an integer of 2 to 6000, for example, an integer of 3 to 5000, or an integer of 4 to 4000, or an integer of 5 to 3000, or an integer of 8 to 2000, or an integer of 10 to 1000, or an integer of 15 to 700, or an integer of 20 to 600, or an integer of 25 to 500, or an integer of 30 to 400, or an integer of 35 to 300, or an integer of 40 to 200, or an integer of 50 to 150, or an integer of 60 to 120, or an integer of 80 to 100, or the numerical value of m may be within the range obtained by combining any two of the above end values.

[0035] According to one embodiment of the present application, in Formula II, n is an integer of 0 to 6000, for example, an integer of 2 to 5000, or an integer of 4 to 4000, or an integer of 5 to 3000, or an integer of 8 to 2000, or an integer of 10 to 1000, or an integer of 15 to 700, or an integer of 20 to 600, or an integer of 25 to 500, or an integer of 30 to 400, or an integer of 35 to 300, or an integer of 40 to 200, or an integer of 50 to 150, or an integer of 60 to 120, or an integer of 80 to 100, or the numerical value of n may be within the range obtained by combining any two of the above end values.

[0036] According to one embodiment of the present application, in Formula II, p is an integer from 2 to 6000, for example, an integer from 3 to 5000, or an integer from 4 to 4000, or an integer from 5 to 3000, or an integer from 8 to 2000, or an integer from 10 to 1000, or an integer from 15 to 700, or an integer from 20 to 600, or an integer from 25 to 500, or an integer from 30 to 400, or an integer from 35 to 300, or an integer from 40 to 200, or an integer from 50 to 150, or an integer from 60 to 120, or an integer from 80 to 100, or the numerical value of p may be within the range obtained by combining any two of the above end values.

[0037] According to one embodiment of the present application, in Formula II, m / (m+n+p)=0.40-0.90, for example, m / (m+n+p)=0.45-0.85, or m / (m+n+p)=0.50-0.80, or m / (m+n+p)=0.55-0.75, or m / (m+n+p)=0.60-0.70, or m / (m+n+p)=0.65-0.68, or the ratio of m / (m+n+p) can be within the numerical range obtained by combining any two of the above end values. According to another embodiment of the present application, in formula II, n / (m+n+p)=0.00-0.20, for example, n / (m+n+p)=0.05-0.15, or n / (m+n+p)=0.06-0.12, or n / (m+n+p)=0.08-0.10, or the ratio of n / (m+n+p) can be within the numerical range obtained by combining any two of the above end values. According to one embodiment of the present application, in formula II, p / (m+n+p)=0.10-0.40, for example, p / (m+n+p)=0.15-0.35, or p / (m+n+p)=0.20-0.30, or the ratio of p / (m+n+p) can be within the numerical range obtained by combining any two of the above end values.

[0038] According to one embodiment of the present application, -SO3B is connected to the ortho, meta or para position of the benzene ring. According to one embodiment of the present application, B is selected from at least one of the following: hydrogen ion, metal cation, ammonium ion, organic amine cation, phosphonium cation, preferably B is hydrogen ion.

[0039] According to one embodiment of the present application, R1 is connected to the ortho, meta or para position of the benzene ring, representing -H or -(CF2) a -CF3, wherein a is an integer from 0 to 6, for example, a is an integer of 0, 1, 2, 3, 4, 5 or 6.

[0040] According to one embodiment of the present application, R2 is connected to the ortho, meta or para position of the benzene ring, indicating -(CF2) b SO3Z, wherein b is an integer from 0 to 6, for example, b is an integer of 0, 1, 2, 3, 4, 5 or 6; Z is selected from at least one of the following: hydrogen ion, metal cation, ammonium ion, organic amine cation, phosphonium cation; preferably Z is a hydrogen ion.

[0041] According to one embodiment of the present application, the equivalent weight of the sulfonic acid functionalized polyfluorinated styrene resin is 500-8000 g / mol, for example, 600-7000 g / mol, or 700-6000 g / mol, or 800-5000 g / mol, or 900-4000 g / mol, or 1000-3000 g / mol, or 1500-2000 g / mol, or within the range obtained by combining any two of the above end values.

[0042] According to another embodiment of the present application, the weight average molecular weight of the sulfonic acid functionalized polyfluorinated styrene resin can be 10,000-1,000,000, for example, 20,000-800,000, or 30,000-600,000, or 40,000-500,000, or 50,000-400,000, or 60,000-200,000, or 80,000-150,000, or 100,000-120,000, or within the numerical range obtained by combining any two of the above end values.

[0043] According to one embodiment of the present application, the sulfonic acid functionalized polyfluorinated styrene resin comprises a component having a structure shown in Formula III:

[0044]

[0045] In formula III, m, n, p, R1, R2 and B are as defined above.

[0046] The present application also provides a method for manufacturing the composite material of the present application. Figure 1 A flow chart of the method is shown, as Figure 1 As shown in the flowchart of FIG. , the method of the present invention comprises:

[0047] Step 1: dissolving the sulfonic acid functionalized polyvinyl fluoride resin and the sulfonic acid functionalized polyfluorinated styrene resin in a solvent to form a solution or dispersion;

[0048] Step 2: coating the solution or dispersion on the surface of the substrate to form a coating film;

[0049] Step three: drying the coating film to obtain the composite material.

[0050] The applicant further emphasizes here that, as can be seen from the above, the method of the present invention is to dissolve the mutually independent sulfonic acid functionalized polyfluoroethylene resin and sulfonic acid functionalized polyfluorostyrene resin that have been separately polymerized in advance in a solvent, and then cast and dry them to form, for example, the desired proton exchange membrane. Therefore, in the formed composite material and proton exchange membrane of the present invention, the above two resins are in a physically mixed state, and there is no covalent bond between the two.

[0051] According to one embodiment of the present application, the solvent used in step 1 is:

[0052] water;

[0053] At least one organic solvent selected from the group consisting of: N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidone, methanol, ethanol, n-propanol, isopropanol, ethylene glycol, propylene glycol, glycerol, n-butanol, isobutanol, and n-hexanol; or

[0054] A mixture of water and one or more of said organic solvents.

[0055] In the case where the solvent is a mixture of water and one or more of the organic solvents, the weight ratio of the weight of water to the total weight of all organic solvents is 1:10-10:1, for example, 1:5 to 5:1, or 1:3 to 3:1, or 1:2 to 2:1, or 1:1, or the weight ratio can be within the numerical range obtained by combining any two of the above end values.

[0056] According to one embodiment of the present application, in the step one, the dissolution is carried out for 0.5-24 hours at a temperature of 10-200°C and a pressure of 0.1-10Mpa; for example, the temperature used for the dissolution may be 20-180°C, or 30-170°C, or 40-160°C, or 50-150°C, or 60-140°C, or 70-130°C, or 80-120°C, or 90-100°C; the pressure used for the dissolution may be 0.2-9MPa, or 0.5-8Mpa, or 0.8-7Mpa, or 0.9-6MPa, or 1-5MPa, or 2-3MPa; the dissolution duration may be 1-22 hours, or 2-20 hours, or 3-16 hours, or 4-12 hours, or 6-8 hours.

[0057] According to one embodiment of the present application, based on the total weight of the solution synthesized in step 1, the solid content of the solution ("total weight of the two resins / (total weight of the two resins+total weight of the solvent)×100%) can be 0.5-50% by weight, or 1-40% by weight, or 5-35% by weight, or 6-30% by weight, or 8-20% by weight, or 10-15% by weight, or the solid content of the solution can be within the numerical range obtained by combining any two of the above end values.

[0058] According to one embodiment of the present application, in step 2, the substrate is selected from one or more of the following: glass, metal (such as stainless steel, copper, etc.), ceramic, plastic, resin (such as expanded polytetrafluoroethylene), fabric, etc.

[0059] According to another embodiment of the present application, in the step 3, the composite material is obtained by drying at a temperature of 20-200° C. for 0.5-24 hours. For example, the drying temperature may be 30-170° C., or 40-160° C., or 50-150° C., or 60-140° C., or 70-130° C., or 80-120° C., or 90-100° C.; the drying duration may be 1-22 hours, or 2-20 hours, or 3-16 hours, or 4-12 hours, or 6-8 hours.

[0060] According to one embodiment of the present application, by selecting a suitable solution solid concentration and a solution application amount, the dry film thickness of the dried film is 1-200 microns, for example, 2-150 microns, or 5-100 microns, or 6-80 microns, or 8-50 microns, or 9-30 microns, or 10-20 microns, or the dry thickness can be within the numerical range obtained by combining any two of the above end values.

[0061] After the drying, the formed composite membrane can be removed from the substrate as needed to obtain a self-supporting proton exchange membrane; or the formed composite membrane can be left unremoved from the substrate, thereby forming a stacked structure, which includes the composite membrane and the substrate, and the substrate can serve as a mechanical support membrane. The composite membrane can be applied on one side of the substrate, or on both sides of the substrate. For example Figure 2A proton exchange membrane having a laminated structure is shown, with a layer of ePTFE membrane as a mechanical support and two layers of composite membranes respectively located on both sides of the ePTFE. In this embodiment, the weight ratio of the membrane formed by the composite material to the expanded polytetrafluoroethylene membrane is 99:1 to 50:50, for example, 95:5 to 55:45, or 90:10 to 60:40, or 85:15 to 65:35, or 80:20 to 70:30, or 75:25 to 72:28, or the weight ratio can be within the numerical range obtained by combining any two of the above end values.

[0062] The composite material, synthesis method and proton exchange membrane of the present invention can achieve one or more of the following advantages:

[0063] 1. Compared with the existing proton exchange membrane, the proton exchange membrane prepared by the physical mixed composite of two resins of the present invention exhibits unexpectedly excellent proton conductivity at a higher temperature;

[0064] 2. The composite material exhibits excellent compatibility, high chemical stability and long service life, and also has good glass transition temperature Tg and mechanical strength;

[0065] 3. The method of the present invention has a simple synthesis process, significantly simplifies the production procedures, and the combination of the two resins greatly reduces the production cost of the proton exchange membrane.

[0066] The present application is described below in the form of specific examples, and its purpose is to better understand the content of the present application. It should be understood that these examples are merely illustrative and non-restrictive. The reagents used in the examples are conventionally purchased from the market unless otherwise specified. The methods and conditions used in the examples are conventional methods and conditions unless otherwise specified.

[0067] Example

[0068] In the following examples, the performance of the ion exchange membranes made of the composite material of the present invention and the prior art materials is compared. The following examples are only specific examples listed in this application, but the technical features of this application are not limited thereto. Any simple changes, equivalent replacements or other modifications made based on this application to solve basically the same technical problems and basically the same technical effects are all covered within the scope of protection of this application.

[0069] The sulfonic acid functionalized polyfluoroethylene resin used in the following examples and comparative examples was purchased from San Ai Fu Company with the trade name FSR-900, which has the structure of formula I, wherein the molar ratio of [-CF2-CF2-] unit to [-CF(-X-SO3A)-CF2-] unit is 4.5:1, -X-SO3A is -[OCF2CF(CF3)]-O[CF2]2-SO3H, and its equivalent weight is 900 g / mol.

[0070] The sulfonic acid functionalized polyfluorinated styrene resin used in the following examples and comparative examples was purchased from San Ai Fu Company with the trade name PTFSA-500, and has the structure of formula III, wherein R1 = -H; R2 = -(CF2)2SO3H; m / (m+n+p) = 0.62, n / (m+n+p) = 0.08; p / (m+n+p) = 0.30, and its equivalent weight = 516 g / mol.

[0071] Example 1

[0072] Weigh 50 g of the sulfonic acid functionalized polyvinyl fluoride resin and 50 g of trifluorostyrene sulfonic acid resin, add them into 900 g of N,N-diethylacetamide respectively, stir and dissolve them at 80° C. and normal pressure (about 0.1 MPa) for 1 hour to obtain a mixed solution of sulfonic acid functionalized polyvinyl fluoride resin and trifluorostyrene sulfonic acid resin.

[0073] The mixed solution was coated on a glass plate using a coating machine, and then the coated film and the glass plate were placed in an oven, heated at 140°C for 1 hour, and then heat treated at 180°C for 1 hour, and then the dried film was peeled off from the glass plate to obtain a dry dense film. The thickness of the film after drying was measured by a thickness gauge (Metricon 2010) to be 15 μm.

[0074] The proton conductivity of the proton exchange membrane was measured at 80°C and 95% relative humidity according to GB / T 20042.3-2009 to be 0.13S / cm. The breaking strength of the dried proton exchange membrane was measured using a universal testing machine to be 58.2MPa, the breaking elongation was 46.5%, and the glass transition temperature was 143°C. The water absorption of the film was measured at 25°C according to GB / T20042.3-2009 to be 85.6%.

[0075] Embodiment 2:

[0076] The steps and process parameters of the example were repeated to prepare a mixed solution of sulfonic acid functionalized polyvinyl fluoride resin and trifluorostyrene sulfonic acid resin.

[0077] A 15 μm thick ePTFE film was used as a substrate, and the solution was coated on both sides of the ePTFE film using a coating machine. The coated film was placed in an oven for drying, and dried according to the same process as in Example 1. The total thickness of the double-sided film after drying was measured by a thickness gauge (Metricon 2010) to be 13 μm.

[0078] According to the same detection technology as Example 1, the proton conductivity of the proton exchange membrane was measured to be 0.09S / cm at 80°C and 95% relative humidity; the breaking strength of the dry proton exchange membrane was measured to be 47.3MPa, the breaking elongation was 45.6%, and the glass transition temperature was 142°C using a universal testing machine; the water absorption of the film was measured to be 85.6% at 25°C.

[0079] Comparative Example 1:

[0080] Weigh 50 g of the sulfonic acid functionalized polyvinyl fluoride resin, add it into 450 g of N,N-diethylacetamide, and stir and dissolve it at 80° C. and normal pressure (about 0.1 MPa) for 1 hour to obtain a solution of the sulfonic acid functionalized polyvinyl fluoride resin.

[0081] The solution was coated on a glass plate using a coating machine, and then the coated film and the glass plate were placed in an oven together, heated at 140°C for 2 hours, and then heat treated at 180°C for 1 hour, and then the dried film was peeled off from the glass plate to obtain a dry dense film. The thickness of the film after drying was measured by a thickness gauge (Metricon 2010) to be 15 μm.

[0082] According to the same detection technology as Example 1, the proton conductivity of the proton exchange membrane was measured to be 0.07S / cm at 80°C and 95% relative humidity; the breaking strength of the dry proton exchange membrane was measured to be 28.1MPa, the breaking elongation was 220%, and the glass transition temperature was 101°C using a universal testing machine; the water absorption of the film was measured to be 67.0% at 25°C.

[0083] Comparative Example 2:

[0084] In this comparative example 2, 50 g of trifluorostyrene sulfonic acid resin was weighed, added to 450 g of N,N-diethylacetamide, and stirred and dissolved at 80° C. and normal pressure (about 0.1 MPa) for 1 hour to obtain a solution of trifluorostyrene sulfonic acid resin.

[0085] The solution was coated on a glass plate using a coating machine, and then the coated film and the glass plate were placed in an oven together, heated at 140°C for 2 hours, and then heat treated at 180°C for 1 hour, and then the dried film was peeled off from the glass plate to obtain a dry dense film. The thickness of the film after drying was measured by a thickness gauge (Metricon 2010) to be 15 μm.

[0086] According to the same detection technology as Example 1, the proton conductivity of the proton exchange membrane was measured to be 0.10S / cm at 80°C and 95% relative humidity; the breaking strength of the dry proton exchange membrane was measured to be 72.3MPa, the breaking elongation was 12%, and the glass transition temperature was 158°C using a universal testing machine; the water absorption of the film was measured to be 112.0% at 25°C.

[0087] From the comparison between the above invention embodiments and the comparative examples, it can be seen that the invention embodiments of the present application, by adopting physical mixing of two resins, synthesize a proton exchange membrane having the following excellent combination of properties by a simple and low-cost production process: excellent proton conductivity at higher temperatures, excellent mechanical strength, suitable glass transition temperature and water absorption.

Claims

1. A composite material, comprising, based on the total weight of the composite material, 40-60 wt% of a sulfonic acid functionalized polyvinyl fluoride resin and 60-40 wt% of a sulfonic acid functionalized polystyrene fluoride resin, wherein the sulfonic acid functionalized polyvinyl fluoride resin and the sulfonic acid functionalized polystyrene fluoride resin are physically mixed with each other; The sulfonic acid functionalized polyvinyl fluoride resin comprises a component having a structure shown in Formula I: Formula I wherein M is an integer from 2 to 5000, N is an integer from 5 to 6000, and the ratio of M to N is 5:95 to 95:5; and X is a divalent group having the following structure: -[OCF2CF(CF3)] x -O[CF2] y -, wherein x is an integer of 1, 2, 3, 4, 5 or 6, and y is an integer of 1-8; A is selected from at least one of the following: hydrogen ion, metal cation, ammonium ion, organic amine cation, phosphonium cation; the equivalent weight of the sulfonic acid functionalized polyvinyl fluoride resin is 500-8000 g / mol; The sulfonic acid functionalized polyfluorinated styrene resin comprises a component having a structure shown in Formula II: Formula II wherein m is an integer from 2 to 6000, n is an integer from 2 to 5000, p is an integer from 2 to 6000, m / (m+n+p)=0.60-0.75, n / (m+n+p)=0.05-0.20; p / (m+n+p)=0.20-0.35; -SO3B is connected to the ortho, meta or para position of the benzene ring, and B is selected from at least one of the following: hydrogen ion, metal cation, ammonium ion, organic amine cation, phosphonium cation; R1 is connected to the ortho, meta or para position of the benzene ring, indicating -H; R2 is connected to the ortho, meta or para position of the benzene ring, indicating -(CF2) b SO3Z, wherein b is an integer of 1, 2, 3, 4, 5 or 6, and Z is selected from at least one of the following: hydrogen ion, metal cation, ammonium ion, organic amine cation, phosphonium cation; the equivalent weight of the sulfonic acid functionalized polyfluoroethylene resin is 500-8000 g / mol.

2. The composite material according to claim 1, characterized in that The sulfonic acid functionalized polyfluorinated styrene resin comprises a component having a structure shown in Formula III: Formula III wherein m is an integer from 2 to 6000, n is an integer from 2 to 5000, p is an integer from 2 to 6000, m / (m+n+p)=0.60-0.75, n / (m+n+p)=0.05-0.20; p / (m+n+p)=0.20-0.35; B is at least one selected from the following: hydrogen ion, metal cation, ammonium ion, organic amine cation, phosphonium cation; R1 represents -H; R2 represents -(CF2) b SO3Z, wherein b is an integer from 1 to 4, and Z is at least one selected from the group consisting of a hydrogen ion, a metal cation, an ammonium ion, an organic amine cation, and a phosphonium cation; The equivalent weight of the sulfonic acid functionalized polyvinyl fluoride resin is 500-6000 g / mol.

3. A method for manufacturing a composite material as claimed in any one of claims 1 to 2, the method comprising: Step 1: dissolving the sulfonic acid functionalized polyvinyl fluoride resin and the sulfonic acid functionalized polyfluorinated styrene resin in a solvent to form a solution or dispersion; Step 2: coating the solution or dispersion on the surface of the substrate to form a coating film; Step three: drying the coating film to obtain the composite material.

4. The method according to claim 3, characterized in that The solvent is: water; At least one organic solvent selected from the group consisting of: N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidone, methanol, ethanol, n-propanol, isopropanol, ethylene glycol, propylene glycol, glycerol, n-butanol, isobutanol, and n-hexanol; or A mixture of water and said organic solvent.

5. The method according to claim 3, characterized in that In the step 1, the dissolution is continued for 0.5-24 hours at a temperature of 10-200° C. and a pressure of 0.1-10 MPa; In the step 2, the substrate is selected from one or more of the following: glass, metal, ceramic, plastic, resin, fabric; In the step three, the composite material is obtained by drying at a temperature of 20-200° C. for 0.5-24 hours.

6. The method according to claim 5, characterized in that The substrate includes an expanded polytetrafluoroethylene film.

7. A proton exchange membrane, comprising a membrane formed by the composite material according to any one of claims 1 to 2.

8. The proton exchange membrane according to claim 7, further comprising an expanded polytetrafluoroethylene membrane, and a weight ratio of the membrane formed by the composite material to the expanded polytetrafluoroethylene membrane is 99:1 to 50:50.

Citation Information

Patent Citations

  • Fluorine-containing proton exchange membrane for fuel cell prepared by using functional fluororesin

    CN101777657A

  • Fluoric proton exchange resins of polytrifluorostyrenes, synthesizing process and application thereof

    CN1346707A